Liver abscess caused by Clostridium perfringens after left hepatic trisectionectomy for perihilar cholangiocarcinoma: a case report - Yuuko Tohmatsu; Mihoko Yamada; Shimpei Otsuka; Katsuhisa Ohgi; Ryo Ashida; Hanako Kurai; Haruna Yasui; Takashi Sugino; Katsuhiko Uesaka; Teiichi Sugiura (Surgical Case Reports, 2023)
Abstract Background Clostridium perfringens sepsis has been reported to have a rapid onset and severe clinical outcome. We herein report a case of C. perfringens sepsis associated with massive intravascular hemolysis after left hepatic trisectionectomy for perihilar cholangiocarcinoma. Case presentation A 72-year-old woman underwent left hepatic trisectionectomy for perihilar cholangiocarcinoma. Her postoperative course was uneventful except for bile leakage. She was discharged on postoperative day (POD) 35. On POD 54, she was readmitted because of abdominal pain with a high fever. Although her vital signs were stable on arrival at the hospital, a laboratory examination showed a severe inflammatory reaction and hemolysis, and she had developed disseminated intravascular coagulation. Abdominal contrast-enhanced computed tomography showed a 70-mm irregular shape and low-density containing air in liver segment 6, which suggested a liver abscess. The abscess was immediately drained of pus containing air. The pus showed multiple Gram-positive bacilli, and two blood cultures showed Gram-positive bacilli and hemolysis. Empirical antibiotic therapy with vancomycin and meropenem was started because C. perfringens was detected from the preoperative bile culture. Four hours after arrival, tachypnea and decreased oxygen saturation were observed. Her general condition deteriorated rapidly with significant hypoglycemia, progressive acidosis, anemia, and thrombocytopenia. Despite rapid drainage and empiric therapy, she died six hours after her arrival. At autopsy, the abscess consisted of coagulation necrosis of liver cells with inflammatory cell infiltration, and clusters of Gram-positive large bacilli were observed in the necrotic debris. C. perfringens was detected in the drainage fluid and blood culture. She was diagnosed with a liver abscess and severe sepsis caused by C. perfringens and treated promptly, but the disease progressed rapidly and led to her death. Conclusions Sepsis caused by C. perfringens can progress rapidly and lead to death in a few hours, so prompt treatment is needed. When patients who have undergone highly invasive hepatobiliary-pancreatic surgery show hemolysis and hepatic abscesses with gas, C. perfringens should be considered the most likely bacterium.